Workload, job control, work relationship, and work-related stress among employees in Sungai Buloh, Malaysia / Muhamad Khalil Omar... [et al.] - Omar, Muhamad Khalil; Aluwi, Ainie Hairianie; Hussein, Norashikin; Mohd, Idaya Husna; Rusdi, Syezreen Dalina (UiTM Cawangan Johor, 2020)
In Malaysia, by 2030, depression has been predicted to be the number one disability and is expected to decrease workplace productivity. Deputy President of Malaysian Mental Health Association, Datuk Dr Andrew Mohanraj mentioned that depression has already dominated the Malaysian workforce and this issue has become a big problem to the country since it is difficult to identify due to its hidden symptoms. The author also made a comparison between employees and entrepreneurs in SME industry. Those entrepreneurs have more commitment to work as they had to work longer hours and tend to have more work-family conflict, compared to normal employees. Therefore, it has been confirmed that those entrepreneurs in SME industry contributed to a large part of employee turnover, poor well-being and the reduction in job's performance. This study was conducted to find out the impact of work-related stress on SME workers in Sungai Buloh. The objectives of the study are to identify the relationship between workload, job control, work relationships and work-related stress. This objective of the study is also to determine which factors (workload, job control and work relationships) are most influenced by work-related stress.